2011
DOI: 10.1039/c1cc14566e
|View full text |Cite
|
Sign up to set email alerts
|

Substituent and counterion effects on the formation of π-dimer dications of end-capped heptathienoacenes

Abstract: We have investigated the impact of the functionalization and the chemical nature of counterions on the π-dimer dications formation in two end-capped heptathienoacenes. Radical cations of an α-substituted heptathienoacene with triisopropylsilyl groups do not π-dimerize, while those of an α,β-substituted heptathienoacene with four n-decyl side chains show a high propensity toward π-dimerization, increased by PF(6)(-) counterions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
16
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 20 publications
2
16
0
Order By: Relevance
“…[43] As seen in Figure 10 ( (Figure 10, bottom), in good agreement with the three experimental bands associated with the formation of the half-oxidized intermediate T2 (Table 2). Therefore, the TD-DFT calculations have reproduced reasonably well the experimental absorption spectra of the ultimate [D4T7C + ] 2 p-dimer dication and the transient T1 and intermediate T2 species formed during the D4T7 oxidation.…”
supporting
confidence: 84%
See 2 more Smart Citations
“…[43] As seen in Figure 10 ( (Figure 10, bottom), in good agreement with the three experimental bands associated with the formation of the half-oxidized intermediate T2 (Table 2). Therefore, the TD-DFT calculations have reproduced reasonably well the experimental absorption spectra of the ultimate [D4T7C + ] 2 p-dimer dication and the transient T1 and intermediate T2 species formed during the D4T7 oxidation.…”
supporting
confidence: 84%
“…For instance, some of us recently demonstrated the formation of p-dimer dications in oxidized tetrathienoacenes, [41] pentathienoacenes, [42] and heptathienoacenes. [43] When compared to a-linked oligothiophenes, the high propensity towards p dimerization of oligothienoacene radical cations can be attributed to the rigid and planar structure that can maximize the intermolecular orbital overlap upon oxidation. Specifically, radical cations of a heptathienoacene a,b-substituted with four n-decyl side groups (D4T7) are shown to exhibit an exceptional capability for p-dimer formation even at room temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3] Since then, the p-dimer of oligothiophenes has attracted much attention to elucidate the electronic structure and conduction mechanism of p-doped polythiophenes. [4][5][6][7][8][9][10][11][12][13][14][15] A similar p-dimerization was also observed and studied both experimentally and theoretically in other stable radical-species, such as tetrathiafulvalene (TTF) radical cations, [16] phenalenyl radicals, [17] tetracyanoethylene (TCNE) radical anions, [17c, 18] tetracyanoquinodimethane (TCNQ) radical anions, [18d, 19] and viologen radical cations. [20] Experimental studies conducted thus far on the p-dimers of oligothiophene radical cations have revealed chain-length dependence [5] and solvent effects [6] on p-dimerization in the solution phases and the structures of the p-dimer in crystalline form.…”
Section: Introductionmentioning
confidence: 83%
“…Furthermore, detailed studies on the dications of bridged oligothiophene dimers12 and thienoacene radical cations13 as models of π‐dimers have also been reported. However, theoretical studies of the π‐dimer on the oligothiophene radical cations have been limited,13b, 14 partly because the most popular density functional theory (DFT) method, B3LYP, is poor at estimating weak intermolecular interactions. Thus, to our knowledge, no detailed studies based on both experiments and theoretical calculations for the quantitative estimation of the attractive and repulsive intermolecular interactions in the π‐dimers of oligothiophene radical cations in solution have been performed.…”
Section: Introductionmentioning
confidence: 99%